Comparing nitrate-N losses through leaching by field measurements and nitrogen balance estimations. - Aparicio, Virginia Carolina (2015)
Nitrogen (N) balance method is a valuable tool for estimating N losses. However, this technique could lead to incorrect estimates of the amount of nitrate (NO3 −N) leaching if processes relevant to N losses are not considered properly. The aim of this study was to compare NO3 −-N leaching losses estimated using an N balance (nonrecovered N, Nne) with data of NO3 −-N leaching losses (Nl). The experiment was made on a Typic Argiudoll soil planted with corn (five growing seasons) under 0, 100, and 200 kg N ha−1. The ceramic soil-water suction samplers were installed (1 m deep). Drainage was estimated by the LEACH-W model. The greatest overestimation with the N balance method occurred for years with annual rainfall below the historical average and at times of high NO3 −-N availability. Future research should focus on investigating mechanisms of N losses relevant under limited water availability.